The Impact of Perceived Quality, Customer Value, and Satisfaction on Brand Loyalty in the Fashion Industry in Jakarta - Juni Iswanto (Westscience Press, 2025)
This study examines the impact of perceived quality, customer value, and customer satisfaction on brand loyalty in the fashion industry in Jakarta. A quantitative approach was employed, with data collected from 135 respondents using a structured questionnaire measured on a five-point Likert scale. Data were analyzed using SPSS version 25, including descriptive statistics, reliability tests, and multiple linear regression. The results indicate that perceived quality, customer value, and customer satisfaction all have significant positive effects on brand loyalty, with customer satisfaction exhibiting the strongest influence. The study provides practical implications for fashion brands, suggesting that enhancing product quality, delivering superior value, and fostering customer satisfaction are essential strategies to strengthen brand loyalty and maintain a competitive edge in Jakarta’s fashion market.